Znaczenie zagospodarowania Bieszczad dla rolnictwa polskiego - Dębicki, Wilhelm (Wydział Prawa i Administracji UAM, 1966)
Ata time of re-examination of the hitherto prevailing assumptions on which rests the perspective plan of agricultural development in Poland — the process of economic reactivization of Bieszczady becomes the subject of special interest and assumes an all national character. Bieszczady is a land of a special kind in all of Europe, Nowhere in Europe shall we find a territory so completely depopulated and in such a high degree desolated and devastated. But Bieszczady constitute at the same time a region, which is at present very strongly permeated with the socialist economic elements (State Agricultural Farms, Production Cooperatives and the State Forest Enterprises). The author, starting on these two premises, discusses the various aspects of economic activization of Bieszczady and analyses critically the effects of the existing re-settlement scheme of said region and puts forward his own suggestions of solving that problem. The author in particular considers that: 1. The territory of Bieszczady is predestined to play the role of a tourist and spa region and consequently it should be transformed into an immense spa-resort of a Swiss type. Such a solution would at the same time help the space programming of the whole region. 2. The natural riches of Bieszczady in the form of its forest and pasture resources are not yet fully taken advantage of. Consequently the author proposes to develop there — on a large scale — cattle breeding. 3. The old tradition of that region ought to be revived. There is plenty of opportunity for regional industrial activities, for all kinds of services (especially of a tourist -spa character).
The Development of Bieszczady and Its Significance for Polish Agriculture